Don't call it quits : turn the job you have into the job you love - Gaynor, Shana Lebowitz (McGraw Hill-Ascent Audio, 2022)
There are other-often better-ways to find fulfillment at work besides leaving your job In Don't Call It Quits, Shana Lebowitz Gaynor draws on her experience writing about career development to show how you can more deeply connect to your work, reclaim agency in your career, and find the freedom and happiness you're seeking-without upending your life with a job change. As Shana explains, you aren't caught between two terrible options: "stick around and suck it up" or leave and hope for something better. You probably have many more choices than you realize. Don't Call It Quits is your how-to guide for exploring those options. You'll finally be able to turn the job you have into the job you love, with smart strategies backed by scientific research and the real-life experiences of workplace experts including social scientists, HR chiefs, and career coaches to high-achieving professionals. Packed with tips that show you how to shape your own work experience, Don't Call It Quits delivers an eye-opening look at what it takes to shift your mindset to get more out of your job-and more out of life.